The Political Economy of Neo-modernisation Rethinking the Dynamics of Technology, Development and Inequality - Baek, Seung Jin (Springer International Publishing, 2018)
'It is of great value to complement the limitations of contemporary mainstream economic growth discourse by exploiting the complex relations between technology, development, and inequality, while concurrently providing a better academic orientation in the era of the upcoming Industrial Revolution.' -Hak-Su Kim, Chairman of the International Leaders Union and Former Under-Secretary General of the United Nations 'The theoretical strategy to present the inter-dynamic relationship between technological changes and inequality evolution by stages of economic development is innovative in explaining the root causes of developmental trajectories that are different for each country. Such an approach can teach developing countries how to establish a vision and select priorities for their mid- to long-term development planning framework.' -Mohamed El Moctar Mohamed El Hacene, Director of the United Nations Economic and Social Commission for Western Asia and Former Minister of Petroleum and Mines, Mauritania Is there a limit to technological advancements? Are technological advancements creating a more equal and fair world? Starting from influential thinkers driving a never-ending evaluation of development discourse - incorporating theories of modernisation, endogenous growth, globalisation, neoliberalism and several others - Seung-Jin Baek answers these questions and sets out practical steps to create societies that are more equal in the Fourth Industrial Revolution. This book explores why Western-centred development strategies are unlikely to bring about similar developmental paths and outcomes in developing economies. By theoretically and empirically assessing the Technology-Development-Inequality nexus, Baek explores why a distorted developmental path has been observed in recent years, with high income countries being associated with rising inequality. This is important reading for all those seeking to understand international development in a twenty-first century context. Seung-Jin Baek is a South Korean Economist, working at various United Nations Economic and Social Commissions. His research focus lies at the nexus of multidimensional inequality and sustainable transformation and is broadly applicable, most notably to the fields of development policy and political economy.